The role of C-type lectin receptors in the recognition of Pseudiminas aeruginosa - Alshahrani, Mohammad (2018)
Cystic fibrosis patients endure serious lung infection caused by colonisation and persistent infection by a wide range of pathogens, most commonly Pseudomonas aeruginosa (PA). One of the factors that facilitates establishment of chronic lung infection is formation of biofilms which are structures resistant to antimicrobial drugs and immune attack. Biofilms are embedded within extracellular polymeric substance (EPS) that maintains the structure of biofilms. PA produces two important polysaccharides Pel and Psl, which have been implicated in promoting biofilm development and biofilm maintenance, respectively, as well as cell aggregation . To the best of our knowledge, there has not been any study showing the presence of specific immune receptors for the recognition of PA biofilms. C-type lectin receptors (CLRs) are pathogen-recognition receptors that contribute to the recognition of infectious agents through the detection of carbohydrates moieties representing a subset of pathogen-associated molecular patterns (PAMPs).